Reducing poverty through use of irrigation: Evidence from rice farming in Benin - Nonvide, Gbêtondji Melaine Armel (My University, 2022)
An emerging body of literature has claimed that poverty is multidimensional and therefore the unidimensional measure cannot serve as a good proxy for poverty. The actual debate is about the inclusion of other dimensions in the poverty analysis framework. Regarding this, the current study examines poverty measurement in rice farming communities in the municipality of Malanville, Benin using both unidimensional and multidimensional poverty indices. It also assesses the effect of involvement in irrigation on multidimensional poverty through an estimation of a two-stage instrumental variable probit model. Results indicate that incidence of monetary poverty was 45.8%. In term of multidimensional poverty, 53.4% of the rice farmers were found to be multidimensionally poor. Overall, the analysis shows lower incidence of poverty for irrigation farmers compared to dry land farmers. We find that the use of irrigation contributes to reducing the likelihood of being multidimensionally poor by 11%. Other determinants include age of the farmer, gender, farm size, use of improved seed, access to credit, off-farm income and market participation. The positive relationship between use of irrigation and poverty reduction justifies the need for irrigation development targeting to implement poverty reduction policies in developing countries.
Keywords: rice; irrigation; multidimensional poverty; two-stage instrumental variable probit model; Benin